Knowledge management the death of wisdom : why our companies have lost it, and how they can get it back - Kransdorff, Arnold. (2012 digital library., 2012)
Conceived less than 20 years ago, Knowledge Management (KM) is the business discipline about which managers perhaps know the least. Having spent pots of money investing in it, the benefits are still marginal. This is because practitioners are still feeling their way. Now that the boom days are temporarily over, it is timely that KM can be more fully exploited, for it conceals an application that is indispensable for the foreseeable struggle ahead--and after, including an overlooked way out of the credit crash dilemma facing those dogmatic decision makers juggling the option between austerity and growth. It's not rocket science. It's a way of doing both, in this case by refocusing on the old-fashioned notion of productivity implied by this book's Chapter 2 heading: Getting from A to B without going via Z. Not the productivity that comes from cutbacks and austerity but the type that frontruns improved competitiveness, sales, and growth.